Pengaruh Ekstrak Etanol Daun Pangi (Pangium edule) terhadap Penyembuhan Luka Bakar pada Tikus Putih (Rattus novergicus) Galur Wistar - I Made Agus Sunadi Putra; Ni Ketut Era Erliana (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Burns is a form of tissue damage caused by contact with sources that have high temperatures such as fire, electricity, and chemicals. Pangi leaves contain chemical flavonoids, alkaloids, sponges, tannins, and terpenoids that can be used as an alternative in the treatment of burns. This study aims to determine the effect of ethanol extract from Pangi leaves on the healing of second-degree burns. The research design used was an experimental method using white rats with Wistar strain as experimental animals. The treatments were made of 4 kinds with 6 repetitions each. Pangi leaf extraction was carried out by maceration method with 95% ethanol. Variations in treatment were positive control using silver sulfadiazine ointment, negative control without treatment, 2.5% ethanol extract of Pangi leaves and 5% ethanol extract of Pangi leaves. Burns were made by using an iron plate heated with Bunsen fire for 2 minutes and then affixed to the back of the rat for 5 seconds until a second burn was formed which was marked by a reddish color and there were bubbles filled with fluid in the wound. Observations were made by looking at and measuring the width of the wound on day 1, day 2, day 4, and day 7. The results showed that the ethanol extract of Pangi leaves accelerated the healing process of second-degree burns in white rats with the Wistar strain. Pangi leaf ethanol extract with a concentration of 5% was more effective than the concentration of 2.5%. It can be concluded that the ethanolic extract of Pangi leaves affects the speed of wound healing in white rats of the Wistar strain and can be considered one of the active ingredients for the treatment of burns.